2018
DOI: 10.3390/nu10111588
|View full text |Cite
|
Sign up to set email alerts
|

Chungkookjang with High Contents of Poly-γ-Glutamic Acid Improves Insulin Sensitizing Activity in Adipocytes and Neuronal Cells

Abstract: We hypothesized that soybeans fermented with Bacillus spp. for 48 h (chungkookjang) would be rich in poly-γ-glutamate (γ-PGA) and would have greater efficacy for improving insulin sensitivity and insulin secretion in 3T3-L1 adipocytes, min6 cells, and PC12 neuronal cells. We screened 20 different strains of B. subtillus and B. amyloliquefaciens spp. for γ-polyglutamate (PGA) production and their anti-diabetic and anti-dementia activities in cell-based studies. Chungkookjang made with two B. amyloliquefaciens s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Several beneficial components of soy products may contribute to the hypoglycemic effect, including isoflavones and soy protein [97]. A cell-based study suggested that soy protein and isoflavones are beneficial for reducing the risk of onset and development of insulin resistance and T2D and a review also showed that fermented soy products may attenuate the progression of T2D by improving insulin resistance and insulin secretion [98,99]. A pooled analysis reported that isoflavones can improve hyperglycemia, glucose tolerance, and circulating insulin concentration, and can also stimulate phosphorylated AMP-activated protein kinase and acetyl-CoA carboxylase to increase glucose uptake and fatty acid oxidation [60].…”
Section: Discussionmentioning
confidence: 99%
“…Several beneficial components of soy products may contribute to the hypoglycemic effect, including isoflavones and soy protein [97]. A cell-based study suggested that soy protein and isoflavones are beneficial for reducing the risk of onset and development of insulin resistance and T2D and a review also showed that fermented soy products may attenuate the progression of T2D by improving insulin resistance and insulin secretion [98,99]. A pooled analysis reported that isoflavones can improve hyperglycemia, glucose tolerance, and circulating insulin concentration, and can also stimulate phosphorylated AMP-activated protein kinase and acetyl-CoA carboxylase to increase glucose uptake and fatty acid oxidation [60].…”
Section: Discussionmentioning
confidence: 99%
“…The different types of chungkookjang demonstrate unique functionalities. Chungkookjang containing high γ-PGA has better efficacy for improving glucose metabolism and neuronal cell survival [ 5 ]. Fermenting with specific Bacillus species to change bioactive components, including the generation of higher γ-PGA, may enhance the functionality of chungkookjang [ 7 ].…”
Section: Chungkookjang Processing and Bioactive Componentsmentioning
confidence: 99%
“…Chungkookjang traditionally made in Sunchang, Chonbuk-Do, Korea, has been reported to promote insulin sensitivity and subsequently to protect against type 2 diabetes and Alzheimer’s disease progression [ 5 , 14 , 15 ]. Subjects who consumed traditionally made chungkookjang (26 g/day) exhibited a decrease in apolipoprotein B compared to those who consumed a placebo ( p < 0.05) in a 12-week randomized clinical trial [ 16 ].…”
Section: Chungkookjang Processing and Bioactive Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that soybeans fermented by Bacillus spp. possess high γ-PGA content that can improve insulin-sensitizing activity in adipocytes and neuronal cells [8]. From available reports, γ-PGA appears to be effective for improving lipid metabolism and glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%